Meningkatkan Seni Baca Al-Qur’an di TPQ Nurul Hidayah Melalui Pembelajaran Qiro’ah - Dewi Qurrota A’yun; Nelud Darajaatul Aliyah; Nailul Ulah Al Chumairoh Machfud; Rahayu Mardikaningsih; Masfufah Masfufah; Laila Badriyah; Siti Nur Halizah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Qiroah as one of the branches of tajweed science plays an important role in ensuring that every santri can read the Qur'an with tartib, correctly, and beautifully. The learning model developed in this service aims to provide santri with an understanding of the importance of tone and tartil when reading the Qur'an, using phonetic to improve the ability to control the santri's voice, and build santri confidence through reading the Qur'an in public with a good and correct tone. The research method used as the basis for this community service is Asset Based Community Development (ABCD) where TPQ students who already have an interest in reading the Qur'an can be developed to beautify the reading accompanied by tajweed science. The results of this community service inform to make some adjustments improve the quality of teaching and learning at TPQ Nurul Hidayah. The theory of phonetics and phonology can be implemented in Qiro'ah education.